2016
DOI: 10.1108/gs-07-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

The study on key influencing factors of mergers and acquisitions performance based on China state-owned listed enterprises

Abstract: Purpose – The purpose of this paper is to analyze the key influencing factors which affect the performance of M & A and the key influencing factors by establishing grey relational sequence model. The results can not only perfect the current existing theoretical system, but also provide theoretical guide for M & A practice. Design/methodology/approach – First of all, this paper analyzes the M & A per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Lee et al (2019) found that in an emerging economy with less developed capital markets and insufficient investor protection, product market competition improves market efficiency for corporate control in an emerging economy, supporting the complementary hypothesis between product market competition and corporate takeover [22]. About the external factors, studies have investigated the impact of board networks (Renneboog and Zhao, 2014; Cai and Sevilir, 2012) [23,24] and executive incentive (Grinstein and Hribar, 2004;Zhao et al, 2016) [25,26] on enterprise M&A behavior. Renneboog and Zhao (2014) investigated the impact of social network on the corporate M&A process from the perspective of board networks, finding that friendly social contacts make the acquirer company more active in the M&A process and that the information gathering ability of directors and interlocking directors can improve the success rate of M&A while shortening the negotiation time [23].…”
Section: The Influencing Factors Of Enterprise Manda Behaviormentioning
confidence: 89%
See 1 more Smart Citation
“…Lee et al (2019) found that in an emerging economy with less developed capital markets and insufficient investor protection, product market competition improves market efficiency for corporate control in an emerging economy, supporting the complementary hypothesis between product market competition and corporate takeover [22]. About the external factors, studies have investigated the impact of board networks (Renneboog and Zhao, 2014; Cai and Sevilir, 2012) [23,24] and executive incentive (Grinstein and Hribar, 2004;Zhao et al, 2016) [25,26] on enterprise M&A behavior. Renneboog and Zhao (2014) investigated the impact of social network on the corporate M&A process from the perspective of board networks, finding that friendly social contacts make the acquirer company more active in the M&A process and that the information gathering ability of directors and interlocking directors can improve the success rate of M&A while shortening the negotiation time [23].…”
Section: The Influencing Factors Of Enterprise Manda Behaviormentioning
confidence: 89%
“…Based on an executive incentive perspective, Grinstein and Hribar (2004) showed that CEOs receive higher bonus incentives when M&A deals are larger, and this incentive makes CEOs put more effort into closing M&A agreements [25]. In addition, Zhao et al (2016) explored the key factors that influence the performance of corporate M&A in state-owned enterprises and found that increasing executive compensation can significantly improve the post-merger profitability of state-owned enterprises [26].…”
Section: The Influencing Factors Of Enterprise Manda Behaviormentioning
confidence: 99%
“…Ou (2016) puts forward an integrated model based on GRA, decision-making trial and evaluation laboratory, analytic network process and the technique for solving a corporate sustainability performance evaluation and ranking problem. Zhao et al (2016b) analyze the key influencing factors which affect the performance of M&A and the key influencing factors by establishing grey relational sequence model. With global market competition, product family design and a platform-based strategy have received a lot of attention for providing sufficient variety of products in an economical way.…”
Section: Grey System Theory In Economic Developmentmentioning
confidence: 99%
“…There are several factors driving the company in making decisions to conduct M&A deals, including the existence of institutional shareholders in the company [5]. Several previous studies have identified that institutional shareholders can influence the decision-making process in the company.…”
Section: Introductionmentioning
confidence: 99%